Consistency and Change: Districts' Efforts to Engage Stakeholders Over Time. Issue 3 (March 2023) - Hall, Michelle; Marsh, Julie; Daramola, Eupha Jeanne
Background: Across families from all backgrounds, and for all students, when parents and the broader community engage in sustained systematic program improvements, schools and districts are more likely to focus on and maintain improvements. As a result, federal and state lawmakers have implemented engagement mandates. The ways in which these mandates are interpreted and implemented influence the success of the engagement practices. Research Design: We conducted a comparative case study and analyzed state representative survey data. Research Questions: How has Local Control Funding Formula (LCFF) local engagement played out over time? What has been learned? What may be facilitating and inhibiting "meaningful" engagement? Conclusions: Through the lens of democratic engagement, we find broad community and district leadership support for the ideals of community engagement. However, we also find that community engagement over time has generally lacked both depth and breadth and was specifically constrained for traditionally marginalized communities. Our analysis also identifies outlier districts that have established ways to implement broader and deeper engagement activities that focus on utilizing their communities as assets. Our research suggests that district leaders and educators need greater support to fully realize these democratic processes.